EARLY DETECTION OF SUBCLINICAL EPIRUBICIN-INDUCED CARDIOTOXICITY USING TWO-DIMENSIONAL SPECKLE TRACKING ECHOCARDIOGRAPHY. (8th October 2012) - Yu, Kang; Lu, Hong-min; Chen, Hai-Yan; Pan, Cui-Zhen; Xianhong, Shu
Abstract : Objectives: To assess the early subclinical epirubicin-induced cardiotoxicity during treatment of non-Hodgkin's lymphoma using two-dimensional (2D) speckle tracking echocardiography (STE). Methods: Thirty-six patients (15 male/21 female) aged 56.88±9.76 with non-Hodgkin's lymphoma were included. Global longitudinal (GS), circumferential (CS) and radial strain (RS) were determined by 2D-STE before and 1 day after the last dose of epirubicin. Results: Despite normal LVEF, after chemotherapy, GS, CS and RS reduced from −17.92±1.93% to −16.59±2.16% (p<0.01), from −20.46±3.39% to −18.01±2.16% (p<0.01), and from 23.90±5.10% to 21.86±6.03% (p>0.05) respectively. Among sex, age, cumulative doses of epirubicin (mg/m 2 ), cigarette smoking, hypertension and diabetes, hypertension was the only negative predictor of LS decrease (p=0.036, 95% CI 0.03 to 4.06), and diabetes was the only negative predictor of CS decrease (p=0.009, 95% CI 1.16 to 7.30). Conclusions: 2D-STE may help to detect Subclinical systolic myocardial abnormalities presented in asymptomatic non-Hodgin's disease patients shortly after epirubicin treatment.